Penerapan Model Pembelajaran Kooperatif untuk Meningkatkan Keterampilan Proses Merencanakan Eksperimen dan Hasil Belajar PKn di SMK Negeri 1 Sakra Tahun Pelajaran 2018/2019 - Ahmad Farijan (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2019)
The background of this study is the incomplete learning outcomes of X.b grade students of SMK Negeri 1 Sakra in the 2018/2019 Academic Year. To solve these problems by applying cooperative learning models in the learning process. This type of research is conducted by PTK (Class Action Research), which is a study in a classroom at a school with an emphasis on the improvement and improvement of learning processes and practices. Data collection techniques used were interviews, observation, use of tests, demonstrations. Data analysis techniques in this study used the analysis of the level of process skills in planning student experiments, scoring.